A Bug or a Feature? The Marginalization of Jewish Identity and Antisemitism in the EDI Landscape of Canadian Higher Education - Marom, Lilach (Canadian Jewish Studies / Études juives canadiennes, 2026)
This paper examines the construction of antisemitism and Jewish identity within equity, diversity, and inclusion (EDI) frameworks in Canadian higher education (HE). Using mixed-methods data from a national survey and semi-structured interviews, it explores how Jewish faculty and staff perceive the treatment of Jewish identity and antisemitism within EDI policies, resources, and action plans in Canadian HE. Survey results show low awareness and comprehensiveness of EDI and institutional policies about Jewish identity and antisemitism, and low satisfaction with institutional responses and support. The interview data further elaborates on experiences of dismissal and avoidance and points to the conditional recognition of Jewish identity and antisemitism within EDI. Overall, the study suggests that antisemitism is missing or marginalized in policies and that Jewish identity is only partially recognized. The study positions this marginalization as a feature of EDI and urges institutions to engage meaningfully with these frameworks to make them more inclusive.